2005
DOI: 10.1021/ma050417v
|View full text |Cite
|
Sign up to set email alerts
|

A SANS Study of 3PEG−LiClO4−TiO2 Nanocomposite Polymer Electrolytes

Abstract: Nanocomposite polymer electrolytes based on a fully amorphous polymer electrolyte (trihydroxypoly(ethylene oxide-co-propylene oxide), known as 3PEG, with LiClO 4 salt) were studied by means of small-angle neutron scattering with the aim to clarify how the filler particles (nanosized TiO2 or Al2O3) are distributed in the polymer. The scattering data show that the particles are not well dispersed but aggregate in fractal, polymer-like structures. The structures, with a fractal dimension of ∼2 on length scales fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Although particle aggregation, typically in the form of fractal aggregates, is known to occur in fumed silica and may occur in the composite electrolytes investigated here, it does not lead to the formation of a percolating layer close to the filler particles of increased conductivity, as has been suggested for TiO 2 [24]. The hydrogen bonding between SiO 2 [29] or TiO 2 [23] and PEO inhibits segmental motion near the surface.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Although particle aggregation, typically in the form of fractal aggregates, is known to occur in fumed silica and may occur in the composite electrolytes investigated here, it does not lead to the formation of a percolating layer close to the filler particles of increased conductivity, as has been suggested for TiO 2 [24]. The hydrogen bonding between SiO 2 [29] or TiO 2 [23] and PEO inhibits segmental motion near the surface.…”
Section: Resultsmentioning
confidence: 61%
“…Addition of ceramic fillers (TiO 2 [17][18][19][20][21][22][23][24], SiO 2 [25][26][27][28][29], Al 2 O 3 [17,18,21,28,[30][31][32][33], K-LiAlO 2 [34][35][36], BaTiO 3 [37,38], MgO [38,39]) to PEO-based electrolytes was claimed to increased RT conductivities by about 2-3 orders of magnitude, increased lithium ion transference numbers, and also improved interfacial [37] as well as mechanical properties [40]. Ion transport properties, thermal transitions and morphology of the composite electrolytes have been shown to depend on the size/mass [31,39] (nano better than micron), surface area and surface nature (acidic/basic/type of surface groups) of the ceramic fillers.…”
Section: Introductionmentioning
confidence: 99%
“…Anion migration may be facilitated with increase of ceria concentration. Recently, small angle neutron scattering experiments [39] suggest that ionic conductivity increases due to the formation of percolating conducting pathways near to filler particles. Theoretically it was also suggested that the ionic conductivity maximum with insulating filler concentration in polymer nanocomposites can be described by percolation theory based on enhanced interface conductivity [40,41].…”
Section: Compositionmentioning
confidence: 99%
“…That is, the highest-aspect-ratio fillers (NRs with aspect ratio = 6.6) improve the conductivity at 10 times lower concentration than spherical NPs (aspect ratio = 1). As described in the Introduction, one possible mechanism, which could explain the conductivity improvement with the addition of nanofillers, is the creation of percolating pathways for ion conduction. Because the percolation threshold is inversely proportional to the aspect ratio, a percolation argument could possibly explain why high-aspect-ratio NRs have higher ionic conductivity at significantly lower concentrations compared to the lower-aspect-ratio fillers.…”
Section: Resultsmentioning
confidence: 99%
“…A third mechanism involves the organization of nanofillers over large length scales. If the interface between the nanofiller and the electrolyte favors ion mobility, then long-range, conductive pathways (i.e., percolating pathways) could provide paths for enhanced ion transport compared to the bulk. …”
Section: Introductionmentioning
confidence: 99%